PRELIMINARY STUDY ON THE KINETIC PROFILE OF SULFAMETHAZINE IN ADULT LOCAL BREED DOG KAJIAN AWAL TENTANG PROFIL KINETIK SULFAMETAZIN PADA PERANAKAN ANJING LOKAL DEWASA - Lazuardi, Mochamad (Jurnal Veteriner, 2007)
The kinetic parameters of sulmethazine in blood plasma were investigated by UV-Vis spectrophotometer at vaious times following intramuscular administration of 50 mg/kg body weight in local breed dog (Surabaya breed x DEnpasar breed). The objectives of this research
Keywords: sulfonamides, half life, pharmakokinetics, dogs, spectrophotometers